Molecular dynamics simulation of frictional properties of Pt cluster on graphite under load - Cörüt, S.; İpek, S. (Frontiers in Mechanical Engineering, 2023)
Structural lubricity, characterized by nearly frictionless behavior at solid incommensurate interfaces with weak interactions, holds significant technological importance. However, various factors can lead to the breakdown of structural lubricity, such as spontaneous reorientation to a commensurate state, applied load, edge effects, deformations, and wear. To overcome these challenges, clusters can be employed at interfaces. With their high Young's modulus and stiffness, clusters can withstand high loads and tolerate elastic deformations. Therefore, Pt cluster, which inherently possess incommensurate contact with graphite surface, are expected to exhibit structural superlubric behavior, even under high loads, as long as they can sustain incommensurate contact. However, our molecular dynamics (MD) simulations have revealed that Pt cluster on graphite can undergo metastable transitions from the incommensurate state to a commensurate state, resulting in a subsequent stick-slip behavior. In the absence of any external load, the Pt cluster has demonstrated the ability to maintain incommensurate contact with almost zero friction force, primarily attributed to its weak interaction with graphite. However, the presence of an applied load force leads to losing of the initial incommensurate contact between the Pt cluster and graphite, resulting in the emergence of high friction forces and the breakdown of structural lubricity with a similar stick-slip behavior to that observed in the comparative simulations conducted for the commensurate state. It becomes evident that the maintenance of incommensurate contact is crucial for achieving superlubric behavior in Pt cluster-graphite systems, while the presence of an applied load force can disrupt this behavior and lead to higher friction forces.